CROSS-CULTURE BRIDGES IN TOURISM: A STUDY ON TRANSLATION STRATEGIES IN INDONESIAN PROMOTIONAL MATERIALS - Riyono, Ahdi; Kurniati, Diah; Mutohhar, Mutohhar; Ma'mun, Nadiah (University of Kuningan, 2024)
Tourism promotion is a type of operative text. The text is structured to influence the reader to visit the tourism destination on offer. The same should also appear in the translated version. The language form of promotional texts is dialogic and persuasive. This study generally aims to explain in depth the translation strategies used in the translation of tourism promotional texts and the translation strategies suitable for the translation of appellative genre texts. This research used qualitative method with deductive and comparative content analysis techniques. The research begins with data collection of tourism promotional texts by looking at their lexicogrammatical features. The data sources came from tourism promotional materials in the form of brochures from the tourism offices of Jepara, and Kudus regencies. The data were analyzed with a functional approach. The findings of this study revealed that the dominant translation technique used to translate tourism brochure texts from both Jepara and Kudus is the literal technique at 75%, and the semantic method at 72%. Thus, the dominant translation strategy or ideology applied by the translators is foreignization ideology, 98%. Furthermore, the results of this study also showed that the functional approach is more suitable for translating tourism promotional materials, because the function of promotional texts is to promote tourism.